Fabrication of polyaniline-carbon nano composite for application in sensitive flexible acid sensor - Seo, Chang Uk; Yoon, Yeojoon; Kim, Do Hun; Choi, Su Yeon; Park, Won Kyu; Yoo, Jin Sun; Baek, Byeongmin; Bin Kwon, Seok; Yang, Cheol-Min; Song, Young Hyun; Yoon, Dae Ho; Yang, Woo Seok (한국공업화학회, 2018)
Many studies have been carried out on sensors for detecting hazardous chemicals. In this study, a sensor for detecting the presence of acid was developed and evaluated. The sensor is composed of carbon materials and polyaniline, which is a conductive polymer. Various candidate carbon materials for the sensor were examined, including graphite, reduced graphene oxide (rGO), and graphene nanoplatelets (GNP). From characterization of carbon material-polyaniline and acid reaction test, it was confirmed that the GNP was the best carbon material for the acid sensor. For practical use, the GNP-polyaniline composite was coated on PET to enable a flexible sensor. (C) 2018 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.